The microbial composition of dried fish prepared according to Greenlandic Inuit traditions and industrial counterparts. (February 2020) - Hauptmann, Aviaja L.; Paulová, Petronela; Castro-Mejía, Josué L.; Hansen, Lars H.; Sicheritz-Pontén, Thomas; Mulvad, Gert; Nielsen, Dennis S.
Abstract: The practices of preparing traditional foods in the Arctic are rapidly disappearing. Traditional foods of the Arctic represent a rarity among food studies in that they are meat-sourced and prepared in non-industrial settings. These foods, generally consumed without any heating step prior to consumption, harbor an insofar undescribed microbiome. The food-associated microbiomes have implications not only with respect to disease risk, but might also positively influence host health by transferring a yet unknown diversity of live microbes to the human gastrointestinal tract. Here we report the first study of the microbial composition of traditionally dried fish prepared according to Greenlandic traditions and their industrial counterparts. We show that dried capelin prepared according to traditional methods have microbiomes clearly different from industrially prepared capelin, which also have more homogenous microbiomes than traditionally prepared capelin. Interestingly, the locally preferred type of traditionally dried capelin, described to be tastier than other traditionally dried capelin, contains bacteria that potentially confer distinct taste. Finally, we show that dried cod have comparably more homogenous microbiomes when compared to capelin and that in general, the environment of drying is a major determinant of the microbial composition of these indigenous food products. Highlights: Different preparation methods result in different microbiota on dried capelin. Industrially dried capelin harbor a comparably homogenous microbiota. The environment of drying determines the microbial composition of dried fish.